A Case Report of Zygomatic Fracture Reconstruction: Evaluation with Orbital Measurements and Models Registration - Khalil Yousof; Mhd Ayham Darwich; Khaldoun Darwich; Ghina Alassah; Ahmed Imran; Hasan Mhd Nazha (Applied Sciences, 2023)
The repair and reconstruction of defects in the craniomaxillofacial region can be particularly challenging due to the complex anatomy, individuality of each defect, and sensitivity of the involved systems. This study aims to enhance the facial appearance and contribute to the reconstruction of the zygomatic arch. This was achieved through virtual planning of the surgery and assessment of clinical matching, including orbital measurements and registration of numerical models. A three-dimensional design of a young female case was generated on a skull model using Mimics® software, and the orbit was isolated using 3-Matic® to assess the reconstructive effect. 3D-printed implants were then surgically placed on the injured region, and Netfabb® software was used to make a virtual registration between the numerical models before and after the intervention. This allowed for the calculation of a deviation of 7 mm, equivalent to 86.23% of the shape restoration rate, to assess the success of the surgery. The computerized method enabled a precise design of the needed plates and analysis of the fixation places, resulting in a satisfactory cosmetic and functional outcome for the patient with minimal complications and good implant stability. Notably, a significant difference was observed in the orbital frontal area after 3 months of surgery (p < 0.001). Within the limitations of the study, these results suggest that virtual planning and customized titanium implants can serve as useful tools in the management of complex zygomatic-orbital injuries.